EFFECT OF HYPOPROTEINEMIA ON TREATMENT OUTCOME IN CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Khan, Atta-ur- Rehman; Sheikh, Moeen -ul-Haq; Intekhab, Kiran (Journal of Ayub Medical College Abbottabad, 2006)
Background: Malnutrition is prevalent on large scale in hospitalized patients which increases morbidity and mortality, reduces the effectiveness of medical treatment in our hospitals and impairs the quality of life significantly. Early diagnosis and treatment of malnutrition is gaining the significance day by day. Methods: A prospective study was carried out to assess the effects of hypoproteinemia malnutrition on the treatment outcome of children with acute lymphoblastic leukemia. One hundred and sixty three patients with Acute Lymphoblastic Leukemia (ALL) below the age of 14 years with L1 and L2 FAB morphology were included in this study. Treatment protocol used was FBM. Patients were classified according to Waterlow classifications of malnutrition (1976). Group-I, as Well-Nourished children (WNC) and Group-II as Mal-nourished children (MNC). Percentages in both groups were found out with respect to total expired, Relapses and completed treatment. Results: In Group-I (WNC) 50 (81.96%) completed treatment and alive, 5 (8.19%) relapsed and 6 (9.8%) expired. In Group-II (MNC) 31(30.39%) completed treatment and alive,8 (7.84%) relapsed and 63 (61.76%) expired. Overall, in WNC group-I 50(30.67%) completed treatment and alive, 5 (3.07%) relapsed and 6(3.68%) expired. In MNC group-II 31 (19.02%) completed treatment and alive, 8 (4.91%) relapsed and 63 (38.65 %) expired. Conclusion: Hypoproteinemia affects treatment outcome in children with acute Lymphoblastic Leukemia. Keywords: Malnutrition, Acute lymphoblastic leukemia, Children, Prognosis, Serum Protein